Gotong Royong in Parenting Practices in Cireundeu Traditional Village - Aliva Fatiha Aqeela; Gina Nurhaliza Firdaus; Maria Natalia Kewa Wanga; Mauizhaturrahmi Mauizhaturrahmi; Nadhifa Dhira Khairunnisa (Early Childhood Education & Parenting, 2025)
This study aims to explore the concept of gotong royong (mutual cooperation) in parenting practices in Cireundeu Traditional Village, Indonesia, which is an integral part of local culture. Through a qualitative descriptive approach, data were collected via observations and interviews with local community members. The findings reveal that gotong royong in parenting involves not only parents but also extended family members and the community, all of whom play crucial roles in supporting children's development. Ethical and moral values are instilled from an early age, and cooperative parenting is expected to broaden children's horizons and improve their self-confidence in social interactions. This research underscores the importance of preserving traditional parenting practices amidst globalization’s challenges and encourages communities to pass down local wisdom in parenting. These findings contribute to the understanding and developing parenting knowledge rooted in Indonesia’s cultural values.